The Aesthetic Characteristics of Contemporary Art in Semarang Gallery, Sangkring Art Space and Kiniko Art Based on Practical Economic and Pure Aesthetic Values - Mujiyono, Mujiyono; Eko Haryanto (Mudra Jurnal Seni Budaya, 2025)
The gallery will select various forms of contemporary artworks based on a range of aesthetic criteria preferences ranging from concept, form, subject matter, relevance to social issues, symbolism, shocking materials, personal feelings, craftsmanship, innovation, current popularity, and others. The selection process for each exhibition dynamically considers these criteria, allowing the gallery to cater to market demands and introduce new aesthetic perspectives to advance Indonesian art. Therefore, this study aims to identify the parameters of aesthetic values used in collecting and exhibiting contemporary art in various galleries in Semarang and Yogyakarta, Indonesia. A descriptive qualitative method with a case study design explored art criticism, formalism, and deconstructivism. The sample population comprised contemporary art created by professional and emerging artists, which was exhibited between 2012 and 2022. Data were obtained from art samples, artists, appreciators, gallery owners, curators, and critics. Owners and curators were required to complete the questionnaire, followed by interviews, documentation, and observation. Conclusions were then drawn by examining the conceptual relationships in each choice of aesthetic value parameters selected by the gallery to identify aesthetic characteristics. The results showed preferences for contemporary reality, uniqueness attached to complex and complicated form processing, technical skills, and exploration of local idioms. Semarang Gallery presented art with unique dimensions beyond mainstream aesthetics. Intellectual ideas can be seen in Andy Dewantoro's 'Isolation', a work demonstrating a metalinguistic concept. The convention of landscape painting, typically characterized by vibrant colours, is challenged and interrogated through scenes rendered solely in black, white, and grey. The artistic mode of art at Semarang Gallery was also more innovative than that of Sangkring Art Space and Kiniko Art, which had several repetitions. Meanwhile, Sangkring Art Space and Kiniko Art focused more on the beauty of visualization than the criticality of visualization. The visual aesthetic in Nurhidayat's "Erotique, Toxique, Exotique" and Anton Afganial's "Uncertainty" present a visual aesthetic that emphasizes poetic functions. These paintings are complex, unified, and intense.